2020
DOI: 10.3389/fgene.2020.01020
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 Variants in Familial Hypercholesterolemia: A Comprehensive Synopsis

Abstract: Autosomal dominant familial hypercholesterolemia (FH) affects approximately 1/250, individuals and potentially leads to elevated blood cholesterol and a significantly increased risk of atherosclerosis. Along with improvements in detection and the increased early diagnosis and treatment, the serious burden of FH on families and society has become increasingly apparent. Since FH is strongly associated with proprotein convertase subtilisin/kexin type 9 ( PCSK9 ), increasing numbers of studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 140 publications
0
20
0
Order By: Relevance
“…Furthermore, gain of function (GOF) mutations in PCSK9 genes are the cause of familial hypercholesterolemia with significantly higher levels of cholesterol in the blood [ 7 ], whereas loss-of-function mutations (LOF) are associated with hypocholesterolemia [ 8 ]. Table 2 presents the most frequent mutations of PCSK9 that naturally occur [ 8 , 9 ].…”
Section: Pcsk9 and Its Inhibitorsmentioning
confidence: 99%
“…Furthermore, gain of function (GOF) mutations in PCSK9 genes are the cause of familial hypercholesterolemia with significantly higher levels of cholesterol in the blood [ 7 ], whereas loss-of-function mutations (LOF) are associated with hypocholesterolemia [ 8 ]. Table 2 presents the most frequent mutations of PCSK9 that naturally occur [ 8 , 9 ].…”
Section: Pcsk9 and Its Inhibitorsmentioning
confidence: 99%
“…Evidence has shown that a gain-of-function variant of PCSK9 is linked to a high level of blood low-density lipoprotein cholesterol (LDL-C) (Seidah et al, 2014), a primary cause of cardiovascular diseases. In contrast, people carrying loss-of-function PCSK9 variants are asymptomatic, showing lower levels of LDL-C and reduced risks of cardiovascular diseases (Guo et al, 2020b). Ding et al (2014a) delivered Cas9/SgRNA targeting Pcsk9 into the mouse liver via injection of AAV8 particles.…”
Section: Gene Editing In Liver Gene Therapymentioning
confidence: 99%
“…PCSK9 is highly conserved among mammals, including chimpanzee, monkey, camel, alpaca, rat, and mouse, with an approximate amino acid identity of 99, 96, 82, 81, 77, and 77%, respectively. The majority of identified gain-of-function and loss-of-function mutations occur in entirely conserved residues, such as gain-of-function mutations D35Y, L108R, S127R, D129G, N157K, R215H, F216L, R218S, A220T, R357H, D374Y, N425S, R468W, R496W and R499H, and lossof-function mutations R104C, R105Q, G106R, G236S, L253F, G316C, N354I and S462P (2, 4,11,12). However, loss-of-function mutations R46L and R93C and gain-of-function mutations R96L, A168E, R499H, and S636R are not conserved between human and mouse or rat PCSK9.…”
Section: Pcsk9 Functionmentioning
confidence: 99%